Dashboard literacy: Understanding students’ response to learning analytic dashboards - Bennett, Liz; Folley, Sue (Proceedings of the International Conference on Networked Learning, 2018)
Dashboards are the graphical interface that manipulate and present data about students’ learning behaviours (attendance, visits to the library, attainment etc.). Although only a few UK HEIs have developed a dashboard for students, most other UK HEIs have an aspiration to develop their use (Sclater 2014). Hence it is timely and significant to understand the ways that students respond to seeing data presented to them in the form of a dashboard. This paper discusses and conceptualises the findings from a small scale study, funded by Society for Research in Higher Education. The study involved twenty-four final year undergraduate students in a single faculty in a UK University. The study focussed on the ways that students interpret and respond to seeing data about their learning presented via a dashboard. Sutton’s (2012) three pillars of feedback literacy: knowing, becoming and acting, were employed to understand the potential of dashboards for supporting students’ motivation towards their learning. The paper suggests that, similar to feedback literacy, there is a type of literacy associated with dashboards that has components of knowing, becoming and acting and that employing these concepts helps us to understand how students’ respond to dashboards. By identifying students' engagement with dashboards as a literacy practice rather than a technical skill or understanding, the paper argues that we need to focus on students' growing identity that is embedded into a sense of being and is individually experienced and constructed. Hence the notion of dashboard literacy suggests that institutions need to work with students to develop their personal and reflective processes to enhance the way that dashboards are interpreted. The paper provides evidence that students may be motivated by seeing their data presented in a dashboard format and this can lead to changes in behaviour which are likely to lead to improved student outcomes and attainment. It also illustrates how students’ engagement with dashboards is highly individual and dependent on their personal disposition and orientation to learning. Hence their use needs to be treated cautiously recognising the power that these tools have to shape impact on students' well-being alongside their potential.